Functional comparison of pacifiers using finite element analysis. - Tesini, David A.; Hu, Linda C.; Usui, Brent H.; Lee, Christopher L. (Tufts University. Tisch Library., 2022)
Keywords: Pacifier, Palate, Finite element analysis, Non-nutritive sucking, Malocclusion, Posterior crossbite.; Springer Open.